2010
DOI: 10.7763/ijesd.2010.v1.38
|View full text |Cite
|
Sign up to set email alerts
|

Study about Effect of Processed Biodiesel in Physicochemical Properties of Mixtures with Diesel Fuel in order to Increase their Antifouling Action

Abstract: In this paper we try to study how processed biodiesel (with hydrophilic polymer) influences the physicochemical properties of their mixtures with diesel fuel. Using specific volumes of these mixtures, we determine humidity, density, kinematic viscosity and heat of combustion in order to investigate the effect of the polymer. The results show that humidity and kinematic viscosity could decrease considerably, so that mixtures of diesel and processed biodiesel become less pollutant to the environment than Diesel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…For purposes of comparison, Table 2 highlights the properties of DESO-ME and WESO-ME with methyl esters of some other seed oils. The literature has shown that a high percentage of linoleic and oleic acid in beneficial for a higher quality biodiesel 29,30 . The oleic and linoleic acid values for both DESO-ME and WESO-ME were 16.6% and 63.5% and 16.6% and 62.1%, respectively.…”
Section: Propertymentioning
confidence: 99%
“…For purposes of comparison, Table 2 highlights the properties of DESO-ME and WESO-ME with methyl esters of some other seed oils. The literature has shown that a high percentage of linoleic and oleic acid in beneficial for a higher quality biodiesel 29,30 . The oleic and linoleic acid values for both DESO-ME and WESO-ME were 16.6% and 63.5% and 16.6% and 62.1%, respectively.…”
Section: Propertymentioning
confidence: 99%
“…2) has been prepared in a quality of 5 g we introduced this amount in a sample of the same jet fuel (as above) of a volume 1000 mL (1L) (5 g of polymer is defined from the limits of chemical additives in liquid fuels which is 1-4 Kg/tn). This sample stays in an environment temperature for 45 minutes and we observe that the polymer remains indissoluble [5]. Next, we filtrate the mixture via the method ASTM D-2276 [7] by using the filtration device Millipore.…”
Section: B Determination Of Physicochemical Properties Of Jp8 With Tpamentioning
confidence: 99%
“…For this aim we introduce in a sample of JP8 the hydrophilic polymer Thermal Polyaspartate Anion TPA for forty five (45) minutes [5]. It is stressed that the volume of JP8 and the mass of the polymer maintain stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, quality standards represent a certain compromise so that all the fuel performance requirements may be satisfied. By controlling the properties of diesel fuel, it is possible to use one grade of fuel in millions of compression-ignition engines [2].In addition, biodiesel has become a fundamentally important area of focus for work in both the scientific and production sectors, since this alternative energy source can reduce the use of conventional fuels [3]. It is particularly important to note that biodiesel (initially biodiesel/diesel blends and ultimately pure biodiesel) is suitable from both an energy standpoint and in terms of environmental friendliness.…”
mentioning
confidence: 99%